The Importance of Online Media toward Physical Education during Covid-19 Pandemic - Guntur Firmansyah; Nurcholis Istiawan; Trinovandhi Setyawan; Paulus Rah Adi Pawitra (International Conference on Science, Education, and Technology, 2021)
Physical education is outlined as learning through motions and should following the right steps so that it will be meaningful for the learners. Moreover, physical education is a proportional and adequate learning program to share learners’ attentions in learning domains, namely psychomotor, cognitive, and affective. This study implemented literature research by collecting online published articles in Google Scholar website in the range of 2020-2021. The possibility of learning on this subject during pandemic is widely open although the school area or environment was not fully supported with infrastructure facilities on online learning. There are several online media could be the options in bracing physical learning, such as by taking the advantages on the features of Google, WhatsApp, Youtube, Zoom, and Telegram. All in all, the collaboration between teacher, students, and parents became the solution to support online learning via online media, considering some areas were not able to implement online learning due to the internet network, infrastructure and facilities, and the lack of teachers’ skills in administering online learning.